PEMBERIAN INSENTIF, DISIPLIN KERJA, IKLIM ORGANISASI DAN KINERJA - Lukman Afrianto (Universitas Riau, 2015)
Incentives, Work Discipline, Organizational Climate and Employee Performance. The research objective is to investigate and analyze the influence of incentives, work discipline and organizational climate on employee performance. The study was conducted at the Department of Transportation Employees Kota Dumai. Quantitative descriptive research type with the number of respondents amounted to 78 people sampled in the study. Data were collected through questionnaires. Analysis of data using multiple linear regression method. The results showed that simultaneously providing incentives, labor discipline and organization Climate significant effect on employee performance. Partially each variable significant effect on employee performance. Variable work discipline is the most dominant factor affect the employee’s performance means more work discipline variables play a role in determining the performance of employees. Results of regression test hypotheses of the study showed that the value of determination coefficient of 0.686. It shows that 68.6% variable incentives, work discipline and organizational climate can explain its influence on employee performance variables at the Department perhu, while the rest is the influence of other variables that are not described in this study.